Post-pandemic Employment Opportunities in Georgia's Hospitality Industry - Maia Meladze; Tamar Koblianidze; Maka Piranashvili; Shalva Alaverdashvili (European Scientific Journal, ESJ, 2022)
The hospitality sector is a major driver of economic growth and job creation. The jobs created in the sector are important for women, young people and migrant workers, which make up a large share of workers in the field. The coronavirus pandemic has greatly slowed the development of the hospitality industry. This study aims at identifying post-pandemic employment problems and opportunities in Georgia’s hospitality sector of business. The survey was performed using qualitative and quantitative research methods. Interviews were conducted with Georgian experts. Online questionnaires were conducted to determine the level of job satisfaction. Observations showed the most difficult situation of travel and hospitality industry since the pandemic, caused by industry pauses and/or shutdowns, when employees were able to use their skills and move to other industries. The results showed more or less satisfaction with working conditions and relationship. But long working hours and low salary lead to employee dissatisfaction.The employer sees the solution to the problem in communication with the educational space and the need to promote professional education, which leads to the solution of the problem, at least in low-ranking positions